2002
DOI: 10.1152/physrev.00022.2001
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Digestive Enzymes

Abstract: The traditional understanding is that an entirely new complement of digestive enzymes is secreted by the pancreas into the small intestines with each meal. This is thought to be necessary because, like food itself, these enzymes are degraded during digestion. In this review we discuss experiments that bring this point of view into question. They suggest that digestive enzymes can be absorbed into blood, reaccumulated by the pancreas, and reutilized, instead of being reduced to their constituent amino acids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
17

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 89 publications
3
56
0
17
Order By: Relevance
“…Therefore, decreases in trypsin expression may be caused by protein breakdown in the intestine by exogenous acid protease, which may result in a decreased dietary stimulus to the gastrointestinal tract neural system and a downregulation of trypsin expression. Rothman et al (2002) pointed out that a large proportion of the digestive enzymes secreted by the pancreas are absorbed into the blood and recycled in the enteropancreatic circulation, which is similar to the enterohepatic circulation. If so, an increased presence of dietary acid protease would elevate levels of circulating proteases, and correspondingly increase protease accumulation in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, decreases in trypsin expression may be caused by protein breakdown in the intestine by exogenous acid protease, which may result in a decreased dietary stimulus to the gastrointestinal tract neural system and a downregulation of trypsin expression. Rothman et al (2002) pointed out that a large proportion of the digestive enzymes secreted by the pancreas are absorbed into the blood and recycled in the enteropancreatic circulation, which is similar to the enterohepatic circulation. If so, an increased presence of dietary acid protease would elevate levels of circulating proteases, and correspondingly increase protease accumulation in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Although this would seem to be highly unlikely, it has recently been suggested that proteins and polypeptide fragments may indeed be absorbed intact through enterohepatic circulation (62). At the present time, however, this should be considered very speculative, and much more research is needed before the role of soy and/or soy proteins on cholesterol regulation is fully understood.…”
Section: Variations In the Composition Of Soy Protein As A Mechanism mentioning
confidence: 97%
“…There is evidence that indicates the presence of an enteropancreatic circulation of digestive enzymes [169]. Digestive enzymes appear to be preferentially absorbed into the bloodstream and then reaccumulated by the pancreas for use again.…”
Section: Reviewmentioning
confidence: 99%